Plethysmographic Loops: A Window on the Lung Pathophysiology of COPD Patients - Radovanovic, Dejan; Pecchiari, Matteo; Pirracchio, Fabio; Zilianti, Camilla; D’Angelo, Edgardo; Santus, Pierachille (Frontiers in Physiology, 2018)
Plethysmographic alveolar pressure-flow (Palv–F) loops contain potentially relevant information about the pathophysiology of chronic obstructive pulmonary disease (COPD), but no quantitative analysis of these loops during spontaneous breathing has ever been performed. The area of the loop’s inspiratory (Ains) and expiratory portion (Aexp), and the difference between the end-expiratory and end-inspiratory alveolar pressure (ΔPalv) were measured in 20 young, 20 elderly healthy subjects, and 130 stable COPD patients. Ains and ΔPalv increased by 55 and 78% from young to elderly subjects, and by 107 and 122% from elderly subjects to COPD patients, reflecting changes in mechanical heterogeneity, lung-units recruitment/derecruitment, and possibly air trapping occurring with aging and/or obstructive disease. Aexp increased by 38% from young to elderly subjects, and by 198% from elderly subjects to COPD patients, consistent with the additional contribution of tidal expiratory flow-limitation, which occurs only in COPD patients and affects Aexp only. In COPD patients, Aexp and ΔPalv showed a significant negative correlation with VC, FEV1, IC, and a significant positive correlation with RV/TLC. The results suggest that the analysis of plethysmographic Palv–F loops provides an insight of the pathophysiological factors, especially tidal expiratory flow-limitation, that affect lung function in COPD patients